2022
DOI: 10.1186/s42523-022-00176-x
|View full text |Cite
|
Sign up to set email alerts
|

Gut microbiota of ring-tailed lemurs (Lemur catta) vary across natural and captive populations and correlate with environmental microbiota

Abstract: Background Inter-population variation in host-associated microbiota reflects differences in the hosts’ environments, but this characterization is typically based on studies comparing few populations. The diversity of natural habitats and captivity conditions occupied by any given host species has not been captured in these comparisons. Moreover, intraspecific variation in gut microbiota, generally attributed to diet, may also stem from differential acquisition of environmental microbes—an under… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
47
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(52 citation statements)
references
References 150 publications
5
47
0
Order By: Relevance
“…We did not observe any effect of sex on both alpha and beta gut microbial diversity of mouse lemurs. Defining the role of sex in shaping lemur microbiomes is challenging since earlier studies provided mixed results, reporting either a significant role of sex ( Perofsky et al, 2021 ) or no sex-dependent effects ( Bornbusch et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…We did not observe any effect of sex on both alpha and beta gut microbial diversity of mouse lemurs. Defining the role of sex in shaping lemur microbiomes is challenging since earlier studies provided mixed results, reporting either a significant role of sex ( Perofsky et al, 2021 ) or no sex-dependent effects ( Bornbusch et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Dr. Sally Bornbusch (Smithsonian's National Zoo & Conservation Biology Institute, USA) emphasized that microbes can also be acquired from the environment by showing that wild ring-tailed lemurs harbored a greater relative abundance of soil-associated microbes than captiveenvironment conspecifics. 6 Thus, both social and environmental transmission can influence gut microbiome composition. This was reinforced by Dr. Aura Raulo (University of Turku, Finland), who reported that among wild wood mice, anaerobic taxa in the microbiome were linked to social patterns, while aerotolerant taxa underlay spatial patterns.…”
Section: Talks and Postersmentioning
confidence: 99%
“…Jonas Torfs (University of Antwerp, Belgium) presented his PhD project on the microbiome‐gut‐brain axis in captive bonobos where he will investigate effects of grooming. Dr. Sally Bornbusch (Smithsonian's National Zoo & Conservation Biology Institute, USA) emphasized that microbes can also be acquired from the environment by showing that wild ring‐tailed lemurs harbored a greater relative abundance of soil‐associated microbes than captive‐environment conspecifics 6 . Thus, both social and environmental transmission can influence gut microbiome composition.…”
Section: Talks and Postersmentioning
confidence: 99%
“…survival and reproductive success) in the wild. This is despite growing evidence that captivity can signi cantly alter, and in many cases simplify, the GM [26,27], including the mycobiome [23,28]. Wild animals are exposed to highly complex and dynamic environments which are very di cult to replicate in captivity, but which shape the GM and interact with host tness [29].…”
Section: Introductionmentioning
confidence: 99%